2017
DOI: 10.1038/s41598-017-04952-7
|View full text |Cite
|
Sign up to set email alerts
|

Mucin 2 silencing promotes colon cancer metastasis through interleukin-6 signaling

Abstract: Downregulation of Mucin 2 (MUC2) expression is associated with early carcinogenesis events in colon cancer. MUC2 plays a role in the progression of colon cancer, and reduced MUC2 protein expression correlates with increased interleukin-6 (IL-6) expression. However, the interaction between MUC2 and IL-6 in colorectal cancer metastasis remains unclear. We systematically analyzed MUC2 and IL-6 expression and determined the survival of cancer patients with high or low MUC2 and IL-6 expression using the Oncomine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…5a, b ), whereas we did not detect the proteins in the quantitative proteomics screen. This loss of MUC2 and DACH1 protein expression us not unique to our experimental model, but also broadly observed in CRC 34 36 . Along similar lines, HLA peptide ligands from numerous DNA damage sensing proteins (ATR, PRKDC, RAD51) and repair proteins (BCR, BRCA1, BRCA2) were also detected only in CRC organoid lines (Fig.…”
Section: Resultssupporting
confidence: 57%
“…5a, b ), whereas we did not detect the proteins in the quantitative proteomics screen. This loss of MUC2 and DACH1 protein expression us not unique to our experimental model, but also broadly observed in CRC 34 36 . Along similar lines, HLA peptide ligands from numerous DNA damage sensing proteins (ATR, PRKDC, RAD51) and repair proteins (BCR, BRCA1, BRCA2) were also detected only in CRC organoid lines (Fig.…”
Section: Resultssupporting
confidence: 57%
“…Improved metabolic dysfunctions could be explained by the induction of Akkermansia . Furthermore, the changes in gene expression observed in the intestine would support such a hypothesis as transcripts of Muc2 , the predominant secreted mucin from the ileum and colon, were increased ( Velcich et al., 2002 ), and Muc2 deficiency in mice is associated with disruption of epithelial homeostasis and the development of colon cancer ( Hsu et al., 2017 ). In combination, our results suggest that ASP has a major role on the gut microbiome, not only altering the production of metabolites with signaling and energetic functions but also potentially strengthening gut barrier function.…”
Section: Discussionmentioning
confidence: 94%
“… 41 In addition, Hsu et al . 42 demonstrated MUC2 suppressed the migration of colon cancer cells in vitro and dramatically diminished liver metastasis in vivo through IL-6 signaling. In concordance with these studies, our data also showed that mRNA expression of MUC2 was decreased in AOM/DSS-treated male mice compared to control male mice.…”
Section: Discussionmentioning
confidence: 97%